PENGARUH TEKANAN ANGGARAN WAKTU, LOCUS OF CONTROL DAN KOMITMEN PROFESIONAL PADA PERILAKU PENURUNAN KUALITAS AUDIT - Intan Wintari, NI Wayan Wiwin; Sukartha, I Made; Nyoman Badera, I Dewa (Buletin Studi Ekonomi; VOL.20.NO.2.AGUSTUS 2015 (PP 83-176), 2016)
The Impact of Time Budget Pressure, Locus of Control and Professional Commitment on the Reduction of Audit Quality Behavior. Reduced audit quality behavior is a serious threat to the auditing profession. Auditing cases, such as Enron Corporation and Worldcom have made the audit rofession to be the public spotlight, which makes the credibility of the auditors increasingly questionable. This study aimed to examine the factors that can cause reduced audit quality behavior such as time budget pressure, locus of control and professional commitment.  The research used questionnaire that was distributed to 70 auditors of BPKP Representative of Bali Province. Method of determining the sample was saturated sampling. The data analysis was conducted by multiple linear regressions, and the results showed that the time budget pressure and external locus of control has a positive influence on reduced audit quality behavior, while internal locus of control and professional commitment have negative effect.   Keywords:  reduced audit quality behavior, time budget pressure, locus of control, professional commitment
Keywords: reduced audit quality behavior, time budget pressure, locus of control, professional commitment